ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR SISWA KELAS IV SDN SE-GUGUS IV KECAMATAN LIMAPULUH KOTA PEKANBARU - Rahmadani, Moetya Tri; Marhadi, Hendri; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: One of several factor which influenced learning process of students is motivation. The objective of this study is to analyze the factors that influence student motivation and to know which one of the most dominant factor affecting students' motivation of fourth grade students of SDN cluster 4 in Limapuluh district Pekanbaru city. This research method is quantitative descriptive. The sampling technique in this research is cluster sampling. The technique of collecting data using questionnaires. Data analysis technique used is descriptive analysis techniques. The results showed that the factors that influence student motivation is divided into two, namely, internal factors and external factors. To find out the analysis of the factors affecting learning motivation comes from internal factors, it can be seen from the response to the survey respondents, 82.2% confidence, interest at 69.7%, 82.7% health, and 72.9% intelligence. From the calculation results of data analysis obtained by percentage of internal factors with the percentage of 76.87% in the category always. While the factors that influence student motivation in terms of external factors each sub-indicators can be seen from the research respondents 77.7% teacher strategies, 85.3% family environment, 85% school environment, and 80.5% the environmental community. From the calculation results of data analysis obtained by percentage of external factors with the percentage of 82.1% to the category of always. From the data analysis it can be concluded that the most dominant factor in influencing learning motivation of fourth grade students of SDN cluster 4 in Limapuluh district Pekanbaru city influenced by external factors.Keywords: Motivation In Learning